We have to solve the following set of equations:

2x – y + z = –3...(1)

2x + 2y + 3z = 2...(2)

3x – 3y – z = –4 ...(3)

(2) - (1)

=>2x + 2y + 3z - 2x + y - z = 2 + 3

=> 3y + 2z = 5 ...(4)

2*(3) - 3*(2)

=> 6x - 6y - 2z - 6x - 6y - 9z = -8 - 6

=> -12y - 11z = -14

=> 12y + 11z = 14 ...(5)

(5) - 4*(4)

=> 12y + 11z - 12y - 8z = 14 - 20

=> 3z = -6

=> z = -2

Substitute in (4)

3y + 2*(-2) = 5

=> 3y = 5 + 4

=> y = 3

Substitute z and y in (1)

2x – y + z = –3

2x - 3 - 2 = -3

=> 2x = 2

x = 1

**The required values are x = 1 , y = 3 and z = -2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now